Factors influencing the growth of informal rental housing in Swaziland: the case of Matsapha peri-urban areas - Matsebula, Bhekithemba M. S. (My University, 2012)
Rental housing significantly shapes housing discourse at the international level. Until recently, housing policy focussed mainly on home ownership to the neglect of rental housing, a situation that negatively affected the housing market. In order for the housing market to be efficient and effective, it needs to strike a balance between home ownership and rental housing. Likewise, rental housing has mainly focussed on the formal component to the neglect of the informal one. Again, this situation has presented numerous challenges as formality and informality are mutually connected. Based on Swaziland in general, specifically Matsapha peri‐urban areas, this study attempts to unpack the pivotal role played by informal rental housing. Although most governments are of the view that informal settlements are problematic hence need to be eradicated, this study views them as a necessary phenomenon that meets the housing needs of millions of the world’s population. It is in the same vein that this study should be understood. The study’s overriding objective is to contribute to the country’s policy and legislative framework relating to housing particularly rental housing and informal settlements. This calls for an analysis of existing policy and legislative framework in terms of adequacy or lack thereof. Based on primary and secondary sources of data, the study presents perspectives of both tenants and landlords in relation to informal rental housing. These are complemented by government (political and technical) perspectives. Findings from the study revealed that informal rental housing is demand‐driven, affordable and means of livelihood. They also brought to the fore the dynamics of informal rental housing. Based on the findings, the study’s recommendations and conclusions showed that although government is moving from modern to postmodern practices, the institutional framework on the ground is not in place. In addition, the lack of democracy in the country's governance structure compounds matters further. Drawing its conceptual framework from both national and international perspectives, the objective is to link informal rental housing to the country’s unique, but complicated land tenure system and governance structure which apply both traditional and modern methods. The national perspectives focus on traditional, modern and postmodern approaches of informal rental housing whereas the international perspectives focus on modernist and postmodernist approaches, location theory, aspiration theory, economic geography factors and urbanisation factors respectively. As the study unfolds, it increasingly becomes clear that housing in general, rental housing in particular in Swaziland has reached an impasse. this plays itself out in government's change from modern to postmodern practices, which is however negatively impacted by the requisite political will and institutional framework to make it work. In advancing housing perspectives, the study attempts to address the country’s lack of understanding of such an important sector which contributes immensely to economic development through the creation of employment opportunities.